The Impact of Selective Logging on Forest Structure and Function - Davis, Olivia; Thompson, Ethan; Clark, Emma (Journal of Selvicoltura Asean, 2024)
Selective logging is a prevalent forest management practice aimed at balancing timber production and conservation. However, its effects on forest structure and function remain a topic of significant concern. This study aims to evaluate the impact of selective logging on the biodiversity, biomass, and ecological functions of forest ecosystems. We employed a comparative analysis method, where forest plots subjected to selective logging were compared to undisturbed control plots. Data were collected on tree species diversity, density, and biomass, alongside assessments of soil health and microclimate conditions. Our findings indicate that selective logging significantly alters forest structure by reducing tree density and species diversity, leading to an overall decline in biomass. Additionally, changes in soil composition and moisture levels were observed, negatively affecting the forest's ecological functions. The results underscore the importance of adopting sustainable logging practices that mitigate adverse effects on forest ecosystems. In conclusion, while selective logging can provide economic benefits, its detrimental impacts on forest structure and function necessitate careful management and monitoring to preserve biodiversity and ecosystem health.